PELAYANAN ANC TERHADAP KEPUASAN PASIEN DI RUMAH SAKIT KELUARGA HUSADA BATAM - Murniawati; Arum Dwi Anjani (Universitas Batam, 2026)
Patient satisfaction in Antenatal Care (ANC) services is an important indicator in assessing the quality of maternal health services, which has a direct impact on the sustainability of visits and pregnancy monitoring. Various factors such as the attitude of health workers, facilities, speed of service, and communication influence patient perceptions of service quality, which if not optimal can lead to decreased visits and increased risk of pregnancy complications. This study aims to determine Antenatal Care Services on Patient Satisfaction at the Husada Family Hospital in Batam City. This study uses a quantitative approach with an observational cross-sectional design. Conducted on May 10 - June 10, 2025 at the Husada Family Hospital in Batam City on 32 pregnant women who were taken by accidental sampling, Data were analyzed using SPSS. The results of the study showed a relationship between the ANC services provided and patient satisfaction at the Husada Hospital in 2025. This can also be interpreted that the better the ANC services are provided, the more patient satisfaction will increase. It is expected that the Husada Family Hospital will conduct periodic patient satisfaction surveys using standardized instruments, to obtain constructive feedback and a basis for continuous improvement in service quality. Keywords: ANC Services, Patient Satisfaction